Pengaruh Electronic Word Of Mouth (Ewom) Terhadap Minat Pembelian Produk Implora dengan Kepercayaan sebagai Variabel Moderasi pada Aplikasi Tiktok Shop - Aprilia Susanti; Edita Rahma Kamila (Institut Nalanda, 2024)
This study aims to analyze the influence of E-WOM on interest in purchasing Implora products with trust as a moderating variable on the TikTok Shop Application. This research uses a quantitative type of research. The number of respondents in this study was 100 respondents. Sampling used accidental sampling. The test tool used is SMART PLS 4. From the results of this test it can be concluded that E-WOM has a significant direct influence on purchase intention. Trust also has a significant influence on purchasing interest. Meanwhile, the Trust does not moderate E-WOM regarding interest in purchasing Implora products on the Tiktok Application.